Experiências urbanas de idosos no centro de João Pessoa. - Dimenstein, Marcela (2014)
The landscape of contemporary cities, included João Pessoa, has been marked by conditions that demonstrate how the scale of man is being lost and how public space is not being guarded as a place for meetings and interaction between individuals. Nevertheless, it is still possible to find people who resist homogenization and standardization of this city model, enjoying their spaces and experiencing them. Accordingly, the aim of this study is to identify people who use and experience the city making the streets, sidewalks and plazas their sites to see and be seen. The focus of the investigation are the elderly and the search location is the center area of that capital. Methodological strategies as field observations and semi-structured interview, important tools in the field of architecture and urbanism were complemented by photography, drawing and photomontage were used. Thus, it is considered that this study rethinks policy issues such as the recent renovation of the central spaces in the city and their use / update the elderly population. Seeks to contribute to research that show the perception of the population in the city, especially from the memories and stories of their elders. Thus it was possible to investigate changes and continuities on the central space, discover elements of the history and culture of the area, such as parties, social relations of work and leisure, transportation, security, and see the relationship between the elderly and the location studied as a devious way to the problem of impoverishment of urban action.